Healthcare accessibility and financial risks for unmet health needs of the older adult population in the republic of Serbia - Nikola Savić; Slobodanka Bogdanović Vasić; Branimirka Aranđelović; Katarina Pavić; Sanja Kocić; Aleksandra Arnaut; Milena Zlatanović; Jelena Stojčević-Maletić; Svetlana Ristić (Frontiers in Public Health, 2026)
Background and objectives Unmet healthcare needs indicate gaps between healthcare services considered necessary and those actually received, reflecting the accessibility of the health system. This study aimed to examine the frequency of unmet healthcare needs and identify Andersen model predictors of unmet needs due to financial and other objective reasons among older adults in Serbia. Materials and methods This cross-sectional study used data from the 2019 Serbian National Health Survey, conducted from October to December 2019 by the Institute of Public Health of Serbia “Dr Milan Jovanović Batut” and the Ministry of Health. The analysis included a representative sample of respondents aged 65 years and older. Results Among 1,116 older adults with unmet healthcare needs, 40.5% reported financial reasons, while 59.5% reported other objective reasons. Most respondents had chronic health conditions, and 39.0% of them reported financial barriers to necessary healthcare (χ 2 = 5.39, df = 1, p < 0.05). Respondents with poor self-rated health were more likely to report financial barriers than those with good self-rated health (OR = 1.492). Financial barriers were also more frequently reported by respondents who had visited their chosen physician (OR = 1.863), used emergency services (OR = 1.869), or used private healthcare services (OR = 2.069). Conclusion Financial constraints represent an important barrier to healthcare access among older adults in Serbia. Designing more accessible healthcare models requires a transparent and comprehensive analysis of the economic position of older people and its impact on obtaining necessary healthcare services.